Adaptive Precoded MIMO for LTE Wireless Communication - Ahmad Fuad, N.; Tiong, Tiong Teck Chai (IOP Publishing Ltd, 2015)
Long-Term Evolution (LTE) and Long Term Evolution-Advanced (ATE-A) have provided a major step forward in mobile communication capability. The objectives to be achieved are high peak data rates in high spectrum bandwidth and high spectral efficiencies. Technically, pre-coding means that multiple data streams are emitted from the transmit antenna with independent and appropriate weightings such that the link throughput is maximized at the receiver output thus increasing or equalizing the received signal to interference and noise (SINR) across the multiple receiver terminals. However, it is not reliable enough to fully utilize the information transfer rate to fit the condition of channel according to the bandwidth size. Thus, adaptive pre-coding is proposed. It applies pre-coding matrix indicator (PMI) channel state making it possible to change the pre-coding codebook accordingly thus improving the data rate higher than fixed pre-coding.